bus-stat-book1

# That is to say for the given values of x we can find

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ient of correlation. Symbolically ≥r 2 225 7. If r=0, the variables are uncorrelated , the lines of regression become perpendicular to each other. 8. If r= +1, the two lines of regression either coincide or parallel to each other m − m2 9. Angle between the two regression lines is θ = t an-1 1 1 + m1m2 where m1 and,m2 are the slopes of the regression lines X on Y and Y on X respectively. 10.The angle between the regression lines indicates the degree of dependence between the variables. Example 2: If 2 regression coefficients are b1= 4 9 and b2 = .What would be 5 20 the value of r? Solution: The correlation coefficient , r = ± b1b2 49 x 5 20 = = 36 6 = = 0.6 100 10 Example 3: 15 3 and b2 = , Find r Given b1 = 8 5 Solution: r = ± b1b2 = 15 3 x 85 9 =1.06 8 It is not possible since r, cannot be greater than one. So the given values are wrong = 226 9.6 Why there are two regression equations? The regression equation of Y o n X is σ Ye = Y + r y ( X − X ) σx (1) (or) Ye = Y + b1 ( X − X ) The regression equation of X on Y is σ X e = X + r x (Y − Y ) σy X e = X + b2 (Y − Y ) These two regression equations represent entirely two different lines. In other words, equation (1) is a function of X, which can be written as Ye = F(X) and equation (2) is a function of Y, which can be written as Xe = F(Y). The variables X and Y are not inter changeable. It is mainly due to the fact that in equation (1) Y is the dependent variable, X is the independent variable. That is to say for the given values of X we can find the estimates of Ye of Y only from equation (1). Similarly, the estimates Xe of X for the values of Y can be obtained only from equation (2). Example 4: Compute the two regression equations from the following data. X 1 2 34 5 Y 2 3 5 4 6 If x =2.5, what will be the value of y? Solution: X Y x2 y2 xy x = X − X y = Y −Y 1 2 -2 -2 4 4 4 2 3 -1 -1 1 1 -1 3 5 0 1 0 1 0 4 4 1 0 1 0 0 5 6 2 2 4 4 4 15 20 20 10 10 9 227 ∑ X 15 = =3 n 5 ∑ Y 20 Y= = =4 n 5...
View Full Document

## This note was uploaded on 01/18/2014 for the course BUS 100 taught by Professor Moshiri during the Winter '08 term at UC Riverside.

Ask a homework question - tutors are online